2021
DOI: 10.1159/000516324
|View full text |Cite
|
Sign up to set email alerts
|

Sutured Scleral Fixation of Posterior Chamber Intraocular Lens in Children under the Age of 9 with Congenital Ectopia Lentis

Abstract: <b><i>Introduction:</i></b> This study aimed to report the visual acuity outcomes and complications of sutured scleral fixation of posterior chamber intraocular lens (IOL) in children under 9 years old with congenital ectopia lentis. <b><i>Methods:</i></b> Twenty-six children (47 eyes) with congenital ectopia lentis were included in this study. The mean age at surgery was 61.6 ± 22.3 months (range, 32–94). Patients underwent lens extraction, anterior vitrectomy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…studied scleral fixated IOL implantation in their series of ectopia lentis, they reported an improvement of median BCVA of 0.82 logMAR (preoperative) to 0.15 logMAR (postoperative) and an improvement of SE; however, a re-surgery rate of 9% for IOL decenteration was reported. [ 14 ] Cai et al . report in their study of 101 eyes of 57 children under 8 years of age who received a cioni-modified capsular ring tension ring and in the bag IOL placement that in the bag placement offers better stability and the reported improvement in postoperative visual outcomes was significantly better, although re-surgery was needed in a very small number of cases (4/101 eyes) for IOL decentration and anterior capsular contraction.…”
Section: Discussionmentioning
confidence: 99%
“…studied scleral fixated IOL implantation in their series of ectopia lentis, they reported an improvement of median BCVA of 0.82 logMAR (preoperative) to 0.15 logMAR (postoperative) and an improvement of SE; however, a re-surgery rate of 9% for IOL decenteration was reported. [ 14 ] Cai et al . report in their study of 101 eyes of 57 children under 8 years of age who received a cioni-modified capsular ring tension ring and in the bag IOL placement that in the bag placement offers better stability and the reported improvement in postoperative visual outcomes was significantly better, although re-surgery was needed in a very small number of cases (4/101 eyes) for IOL decentration and anterior capsular contraction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cardiovascular manifestations of Marfan syndrome such as aortic root dilation or aortic dissection may threaten their lives. All surgeries were performed by the same surgeon and conducted using phacoemulsification, which presented better clinical outcomes and fewer complications compared to traditional intracapsular and extracapsular cataract extraction [14] , and implantation of a sclera-fixated intraocular lens (IOL) [15] . All eyes underwent bilateral presenting vision test, best-corrected visual acuity (BCVA) test and slit-lamp examination before and after operation.…”
Section: Subjects and Methods Ethical Appovalmentioning
confidence: 99%
“…Besides, no suture-related complications, including erosion or breakage, were noted during the follow-up period in our series. Late subluxation or dislocation of sutured scleral fixation of IOLs has been documented [21][22][23][24] , especially occurring in young patients [21][22]24] . This may be related to suture erosion, scleral tissue cutting by sutures, suture cutting by IOL haptics, IOL haptics cutting by sutures, suture damage by surgical manipulation, and degradation of the suture material itself.…”
Section: Scleral Fixation Of Existing Intraocular Lensmentioning
confidence: 99%
“…A clinicopathological study suggested that the surface properties of the positioning holes of IOLs lead to cutting of sutures, and subsequent subluxation of IOLs [23] . In addition, suture breakage typically occurs after 10y postoperatively and in young patients [21][22]24] . Nevertheless, suture degradation of 10-0 polypropylene cannot be neglected.…”
mentioning
confidence: 99%